Prognostic value of serum apolipoprotein A-I in locally advanced cervical squamous cell carcinoma treated with radical chemoradiotherapy - Chang, Hui; Chen, Kai; Lin, Yan-Zhu; Tao, Ya-Lan; Liu, Yang; Cao, Xin-Ping; Ye, Wei-Jun (Translational Cancer Research, 2018)
Background: Distant metastasis (DM) remains the major cause of death from locally advanced cervical squamous cell carcinoma (CSCC). This study aimed to evaluate the predictive value of pretreatment serum lipids on DM and death, in patients with locally advanced CSCC. Methods: In this study, a total of 331 consecutive patients with stages IIB–IVA CSCC and completed record of radical concurrent chemoradiotherapy (CCRT) were involved between January 2011 and June 2013. Pretreatment serum lipid indexes including total cholesterol (TC), triglyceride (TG), high-density lipoprotein cholesterol (HDL-c), low-density lipoprotein cholesterol (LDL-c), apolipoprotein A-I (apoAI) and apolipoprotein B (apoB) were analyzed for their association with the overall survival (OS), the local-recurrence-free survival (RFS), the distant-metastasis-free survival (MFS) and the disease-free survival (DFS), together with clinical features [age, stage, parametrial invasion, tumor diameter, lymph node metastasis, hemoglobin, squamous cell carcinoma (SCC) antigen and carbohydrate antigen 125 (CA125)]. Results: After univariate and multivariate analysis, serum apoAI level (≥1.2 vs.